2000
DOI: 10.1128/jb.182.22.6509-6513.2000
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli TehB Requires S -Adenosylmethionine as a Cofactor To Mediate Tellurite Resistance

Abstract: The Escherichia coli chromosomal determinant for tellurite resistance consists of two genes (tehA and tehB) which, when expressed on a multicopy plasmid, confer resistance to K 2 TeO 3 at 128 g/ml, compared to the MIC of 2 g/ml for the wild type. TehB is a cytoplasmic protein which possesses three conserved motifs (I, II, and III) found in S-adenosyl-L-methionine (SAM)-dependent non-nucleic acid methyltransferases. Replacement of the conserved aspartate residue in motif I by asparagine or alanine, or of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 48 publications
(37 reference statements)
1
35
1
Order By: Relevance
“…Thus, a putative role of SUMT in K 2 TeO 3 resistance would be the utilization of Te as a substrate and to catalyze the transfer of methyl groups from SAM to the metalloid. In this context, some work from other authors has indicated that the gene products of the tpm and tehB genes from Pseudomonas syringae and E. coli, respectively, are able to biomethylate tellurium (Cournoyer et al, 1998;Liu et al, 2000). Unfortunately, we were unable to detect the genesis of methylated tellurium derivatives in the headspace of cells cultured in the presence of tellurite or tellurate.…”
Section: Cobacontrasting
confidence: 45%
“…Thus, a putative role of SUMT in K 2 TeO 3 resistance would be the utilization of Te as a substrate and to catalyze the transfer of methyl groups from SAM to the metalloid. In this context, some work from other authors has indicated that the gene products of the tpm and tehB genes from Pseudomonas syringae and E. coli, respectively, are able to biomethylate tellurium (Cournoyer et al, 1998;Liu et al, 2000). Unfortunately, we were unable to detect the genesis of methylated tellurium derivatives in the headspace of cells cultured in the presence of tellurite or tellurate.…”
Section: Cobacontrasting
confidence: 45%
“…In other species, the YeaR domain is present as an aminoterminal extension in homologs of the E. coli TehB protein, an S-adenosylmethionine-dependent non-nucleic acid methyltransferase involved in resistance to tellurite (28). This YeaRTehB fusion protein is annotated as "TehB" in several genome sequences (e.g., locus tag YPTB1947 in Y. pseudotuberculosis IP32953 and locus tag spr0880 in S. pneumoniae R6).…”
Section: Resultsmentioning
confidence: 99%
“…The kanamycin ⍀ cassette replacing Alvin_3072 therefore most likely also prevents formation of the Alvin_3073-encoded transporter, and more experiments are needed to exactly dissect the effect exerted by the interposon. The protein Alvin_3073 belongs to a family of transporters that includes a malate uptake system in the yeast Schizosaccharomyces pombe (63), a tellurite resistance protein in Escherichia coli (64), and notably, a sulfite efflux pump in Saccharomyces cerevisiae and other fungi, including Aspergillus fumigatus (65). Alvin_3072 is conserved in several sulfide-oxidizing bacteria (see Fig.…”
Section: Resultsmentioning
confidence: 99%